THE PRESIDENT OF THE REPUBLIC IN THE CONSTITUTIONAL ORDER OF SERBIA – TEN YEARS OF THE CONSTITUTION OF 2006 - Đorđević, Aleksandar S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
It is undoubted that the President of the Republic of Serbia represents the most controversial issue debating in constitutional theory and practice. We can find completely opposite attitudes toward the constitutional status of the President of the Republic: on one hand, the prevailing opinion that the President of the Republic has an active role in the executive branch of the government, but on the other hand, the opinion that the President of the Republic is a figurehead and has only a moderating role. If we remain focused only on normative analysis, there is no doubt that we will be brought to a conclusion that the constitution-maker insisted on the moderating role of the President of the Republic making him an independent constitutional body providing the balance in the system of government. In the constitutional practice, in the previous ten years, we have been in a position to see two totally different “stiles of presidency”. None of them is in accordance with the “constitutional picture” of the institution. From 2007 to 2012 president Tadić was a central constitutional figure. He tended to concentrate all constitutional powers in his hands using the position of the leader of the strongest political party. With comming into power president Nikolic, who gave up the function of the president of the party, constitutional and political power moved almost completely to the president of the Government. The president of the Republic acts sometimes as he has less power than the Constitution gives him.